2009
DOI: 10.1097/scs.0b013e3181955244
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Relationship Between the Severity of Metopic Synostosis and Speech and Language Impairments?

Abstract: The occurrence of cognitive impairment and behavioral problems in patients with metopic synostosis has been described. The relationship between the severity of metopic synostosis and the incidence of speech and language delays has not been established. Twenty patients with nonsyndromic isolated metopic synostosis were evaluated. Five different preoperative measurements (metopic angle at the roof of the orbit, angle of lateral orbital wall at the sella, cranial indices, and distances between medial orbital wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 12 publications
0
20
0
2
Order By: Relevance
“…Given the mixed findings from previous studies, 4,6,9,12,13,15,23,34,41,48 the primary aim of this investigation was to determine whether school-age children with SSC, all of whom underwent cranioplasty, have deficits in language and memory skills in relation to demographically similar children without a craniofacial disorder. Use of a control group for such comparisons is critical but has been rarely undertaken in previous research on this topic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the mixed findings from previous studies, 4,6,9,12,13,15,23,34,41,48 the primary aim of this investigation was to determine whether school-age children with SSC, all of whom underwent cranioplasty, have deficits in language and memory skills in relation to demographically similar children without a craniofacial disorder. Use of a control group for such comparisons is critical but has been rarely undertaken in previous research on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the study's design is limited in its ability to elucidate the mechanisms by which SSC or factors associated with SSC (e.g., surgery and anesthesia exposure 35 ) have led to the group differences observed here and elsewhere. 4,6,9,13,15,23,34,41,48 The etiology of the neurodevelopmental consequences and correlates of SSC remains unclear, with some hypotheses focusing on the effects of the fused suture on brain development [1][2][3]47,49 and others emphasizing preexisting neuropathology that may affect both brain and cranium. 5,19 These studies provide some evidence that changes in brain morphology present prior to surgery persist after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Shipster et al 32 observaron funcionamiento cognoscitivo normal, mientras que otros reportan alteraciones en el lenguaje [32][33][34][35][36] , en la cognición 33,36 , en la motricidad 36 y en la conducta 33 . El hallazgo más frecuente es el déficit en el lenguaje, los distintos estudios mencionan porcentajes variables de pacientes con estas alteraciones, desde el 30% 33,35 hasta el 50% 32,34 . También se menciona que los pacientes con craneosinostosis simple tienen de 1,5 a 2 veces mayor probabilidad de presentar alteraciones cognitivas, de lenguaje y motoras que en la población normal 36 .…”
Section: Etapa Preescolarunclassified
“…La mayoría de los estudios que mencionan el funcionamiento cognoscitivo en esta edad no tienen grupo control [32][33][34][35] y algunos las muestras son pequeñas para establecer una relación causal entre las alteraciones encontradas y la craneosinostosis 34,35 , además el estudio de Mendonca 35 no establece el instrumento que utilizó para evaluar el lenguaje. …”
Section: Etapa Preescolarunclassified
“…Some surgeons have speculated that premature cranial suture fusion leads to alterations in cerebral blood flow, which in turn result in cognitive, speech, language, and/or behavioral problems, but this suggestion remains a point of controversy. 4,5,[14][15][16]20,22,[24][25][26]32,33 Others have speculated that reduced intracranial volume and/ or elevated intracranial pressure impair brain development. 9 However, Hill et al 12 recently demonstrated that intracranial volume constraint was not responsible for alterations in brain function.…”
Section: Radiographic Assessmentmentioning
confidence: 99%